Avaliação de parâmetros limnológicos em reservatórios do semiárido cearense: uma proposta de índice de estado trófico - Silva, Thiago Teixeira da (2024)
The widespread use of water in human life makes its quality necessary, aiming for the well- being of the population, fauna and flora. Natural or artificial reservoirs are great sources of water storage, widely used for supply and irrigation. A recent study states that reservoir waters will still be essential for the next 30 years, due to the expected increase in demand. In reservoirs in the semi-arid region, aspects of non-quality of these waters are observed, both due to quality standard reference values indicated by CONAMA, and resulting from the evaluation of indices, such as IET and IQA. With these characteristics, the Brazilian Semiarid region has a non- abundant amount of water in its reservoirs and with low quality in several points. To assist in decision-making on appropriate initiatives to resolve this problem, this work sought to develop a new IET taking into account data and reservoir conditions in the semi-arid region of Ceará, evaluating 18 parameters through standard procedures and the correlations between them. The data was made available by COGERH, in the years 2014 – 2022, for 25 reservoirs managed by the company. Descriptive statistics were performed for each set of parameter data, removing outlier values to evaluate their variation trends in the reservoirs. An exploratory study was also carried out, studying correlations for parameters versus transparency, in order to build the proposed index, with appropriate adaptations to Carlson's (1977) expressions. The parameters analyzed had high variability in their measurements, with the occurrence of extremely high values in some parameters, such as cyanobacteria counts, even being in disagreement with a federal resolution. In the data collection carried out, the maximum transparency measurement observed in the Pentecoste reservoir was selected to guide the adaptations in Carlson's expressions (1977). Phosphorus was identified as the main limiting nutrient in 80% of the reservoirs. The parameters total phosphorus, total nitrogen, chlorophyll a and turbidity presented the most significant correlations (greater than 0.4) for the composition of the new proposed IET. An adaptation was made to the base expression of the IET, to be associated with values obtained in the semi-arid region. Trophic classes were proposed for this new IET, with their respective expressions and trophic state ranges, subsequently compared with other existing classifications. Statistical analyses, such as PCA and Spearman coefficient, helped to understand the correlations between variables. The proposed new Trophic State Index was created combining traditional and new parameters, showing results consistent with the specific situation of the reservoirs under study, in addition to similar results in determining the trophic state of the reservoirs studied (when comparing with already established indices), suggesting that the new IET can be used to monitor state reservoirs.